Unternehmen Bourdieu: Ein Erfahrungsbericht - Schultheis, Franz (transcript, 2019)
The »Bourdieu phenomenon« in a new light. In his long and close collaboration with Pierre Bourdieu, Franz Schultheis has been able to gain insights into his life and work that open up a largely unknown perspective. In contrast to the usual portraits of Bourdieu as an outstanding social scientist, here the »patron« of a sociological workshop appears on the scene. The description of various aspects of the everyday practice of his Centre de Sociologie Européenne assumes the character of an »ethnography« of working with Bourdieu. Crucial to him, but diametrically opposed to his own fame, is the ideal of the »collective intellectual«, and the attempt to realize it in research and political commitment.